Regional differences in human papillomavirus type 52 prevalence among Japanese women with cervical intraepithelial neoplasia. (6th August 2022) - Kukimoto, Iwao; Onuki, Mamiko; Yamamoto, Kasumi; Yahata, Hideaki; Aoki, Yoichi; Yokota, Harushige; Konnai, Katsuyuki; Nio, Ai; Takehara, Kazuhiro; Kamiura, Shoji; Tsuda, Naotake; Takei, Yuji; et al.
Abstract: Although geographical differences in the distribution of human papillomavirus genotypes have been observed worldwide, no studies have reported on national differences in the prevalence of human papillomavirus types in Japan. Here, we report a cross-sectional study to explore regional differences in the prevalence of human papillomavirus types among Japanese women with cervical intraepithelial neoplasia or invasive cervical cancer. Using human papillomavirus genotyping data from the nationwide prospective study on human papillomavirus vaccine effectiveness, we compared the frequency of detection of 15 high-risk and two low-risk human papillomavirus types in each disease category between the women who visited hospitals located in eastern Japan and those who visited hospitals located in western Japan. The risk of cervical intraepithelial neoplasia progression was assessed by calculating a prevalence ratio of each human papillomavirus type for cervical intraepithelial neoplasia grade 2/3 versus grade 1. Among the human papillomavirus types studied, human papillomavirus 52 was detected significantly more frequently in western hospitals than in eastern hospitals in cervical intraepithelial neoplasia grade 1 patients, but was less frequent in cervical intraepithelial neoplasia grade 2/3. The prevalence of particular human papillomavirus types was not significantly different between patients in hospitals in eastern Japan and those in hospitals in western Japan for invasive cervical cancer. In both eastern and western hospitals, a higher risk of cervical intraepithelial neoplasia progression was observed in patients infected with human papillomavirus 16, 31 or 58. In contrast, there was a significantly higher prevalence of human papillomavirus 52 infection in women with cervical intraepithelial neoplasia grade 2/3 than in those with cervical intraepithelial neoplasia grade 1 in eastern hospitals (prevalence ratio, 1.93; 95% confidence interval, 1.48–2.58), but not in western hospitals (prevalence ratio, 1.03; 95% confidence interval, 0.83–1.30). Regional differences of human papillomavirus 52 prevalence in cervical intraepithelial neoplasia lesions may exist and emphasize the importance of continuous monitoring of human papillomavirus type prevalence throughout the country in order to accurately assess the efficacy of human papillomavirus vaccines. Abstract : We investigated regional differences in the distribution of human papillomavirus types in Japan. Human papillomavirus 52 might be more prevalent in western Japan than in eastern Japan in cervical intraepithelial neoplasia grade 1, but less prevalent in cervical intraepithelial neoplasia grade 2/3.